Artificial lights with different spectra do not alter detrimental attraction of young Chinook salmon and sockeye salmon along lake shorelines. (26th August 2021) - Tabor, Roger A.; Perkin, Elizabeth K.; Beauchamp, David A.; Britt, Lyle L.; Haehn, Rebecca; Green, John; Robinson, Tim; Stolnack, Scott; Lantz, Daniel W.; Moore, Zachary J.
Abstract: Tabor RA, Perkin EK, Beauchamp DA, Britt LL, Haehn R, Green J, Robinson T, Stolnack S, Lantz DW, Moore ZJ. 2021. Artificial lights with different spectra do not alter detrimental attraction of young Chinook salmon and sockeye salmon along lake shorelines. Lake Reserv Manage. 37:313–322. Artificial light at night (ALAN) is common in lakes with developed shorelines, especially prevalent in the nearshore areas where juvenile fishes, including salmonids, are present. One concern is that fishes may be attracted to ALAN and become more vulnerable to predators. The use of longer wavelength lights has been suggested to reduce the effects of ALAN; however, the response in juvenile salmonids is not well known. We tested the hypothesis that longer wavelength lights would attract fewer subyearling Chinook salmon ( Oncorhynchus tshawytscha ) and sockeye salmon ( O. nerka ) than shorter wavelength lights. Test lights included 4 LED lights, an incandescent light, and a high-pressure sodium light (HPS). In total, 13 experimental trials were conducted in 2017 and 2018, and in total 1769 Chinook salmon and 870 sockeye salmon were collected with beach seines. The mean catch rate (number per beach seine set) of subyearling salmonids was 51.0 for lighted treatments but only 6.6 for control treatments (no light). In both years, we did not find any significant difference in catch rates for either species between either of the longer wavelength lights (red-filter and yellow-filter LED lights) and other lights, and thus we rejected the hypothesis that longer wavelength light would attract fewer subyearling salmonids. For these early life stages of salmon in shallow shoreline habitats, reducing the intensity of light present is likely more important than altering the spectral composition when trying to minimize maladaptive attraction to ALAN.